PENURUNAN KANDUNGAN LOGAM PB DAN CR LEACHATE MELALUI FITOREMEDIASI BAMBU AIR (EQUISETUM HYEMALE) DAN ZEOLIT - Bambang Suharto; Liliya Dewi Susanawati; Betha Ika Wilistien (Agroindustrial Technology, University of Trunojoyo Madura, 2011)
The very large numbers of trash in the TPA (end disposal place) will cause the natural decomposition process goes on massively as well. The decomposition process will change trash into organic fertilizer that if there any water input from the outside, it will dissolve metals that later become the byproduct that is leachate. The introduction of chemical contained in the leachate into the waters ecosystem may also affect the existing biota. Therefore, it is need the waste treatment before released into the environment. Leachate waste treatment by using the phytoremediation principle by means of Bambu air plant (Equisetum hyemale), with zeolite planting media was to be the choice in the effort of liquid waste treatment the Phytoremediation system was taken with a various considerations that very potential to develop into new innovation in the process of leachate waste treatment.This research had the purpose to know the effectiveness of phytoremediation system using water bamboo plant (Equisetum hyemale) and zeolit planting media by batch system and continue system in reducing Pb and Cr heavy metals contents of leachate. Research method used was the experimental method. Observations carried out involved environmental temperature and humidity, solution pH and treatment temperature, Reduction of Pb and Cr Metals Contents on leachate.Batch system and continue system as a whole, mean of leachate pH tested during this treatment was about 7,466. Leachate pH tested did not less than 7,200 and not more that 7,810. Mean of leachate temperature from the first week through third week was of 22,283°C. The best treatment was on the K2S1 (60 batch system plants) treatment with reduction of Pb metal content of 82,2% in the last week of observation. While the reduction of Cr metal of 61,2% was on the K2S2 (60 continue system plants) treatment.